Functionalized graphene quantum dots for dye-sensitized solar cell: Key challenges, recent developments and future prospects - Mahalingam S.; Manap A.; Omar A.; Low F.W.; Afandi N.F.; Chia C.H.; Rahim N.A. (Elsevier Ltd, 2023)
Biomechanics; Chemical modification; Electron transport properties; Graphene; Graphene quantum dots; Nanocrystals; Nanostructured materials; Quantum chemistry; Semiconductor quantum dots; Substitution reactions; 'current; Development prospects; Dye- sensitized solar cells; Electron transport; Functionalizations; Functionalized graphene; Future prospects; Performance; Property; Thermal and mechanical properties; Dye-sensitized solar cells